Controls of nitrogen spiraling in Kansas streams - O'Brien, Jonathan M. (Kansas State University, 2006)
We used a series of whole stream experiments to quantify the impacts of inorganic-nitrogen concentration on stream nitrogen cycling and transport in prairie streams. We conducted 15NO3- stable isotope tracer experiments to measure the nitrogen cycling dynamics in 9 streams with a wide range (over 5 orders of magnitude) of nitrate concentrations. The major nitrogen-transforming processes, including uptake, nitrification, and denitrification, increased approximately 2 to 3 orders of magnitude and did not show signs of Michaelis-Menten type saturation across streams. Denitrification only accounted for a small proportion of total nitrate uptake. The observed functional relationships of biological nitrogen transformations and chronic nitrate concentration were best described by a Log-Log relationship. A series of inorganic-nitrogen addition experiments were conducted to quantify the impacts of acute nitrogen inputs on nitrogen cycling. These experiments showed that uptake saturated in response to short-term pulses of nitrogen. Ambient concentrations of ammonium and nitrate were less than their respective half-saturation coefficients, and uptake rates were less than 5% of Vmax, suggesting severe limitation of nitrogen. The saturation of uptake due to acute nitrogen inputs contrasts with uptake associated with chronic inputs of nitrate, which was not found to saturate. Chamber experiments and whole-stream ammonium addition experiments demonstrated that uptake and mineralization of ammonium varies spatially within the stream channel, occurring predominantly in riffles as opposed to pool habitats. The total transport distance of nitrogen and carbon within prairie streams was estimated based on field measurements and nutrient spiraling theory. Transport of organic nitrogen was dominant in prairie streams, as compared to inorganic nitrogen transport, both in terms of total concentration and transport distance. These results indicate that although carbon and inorganic-nitrogen were highly conserved in these headwater streams, organic-nitrogen was much more readily transported.
Keywords: Stream; Nitrogen; Konza; Biogeochemistry; Biology, Limnology (0793)